Prolactin response to tryptophan during mianserin treatment. - Cowen, P (1988)
Unlike tricyclic antidepressants and monoamine oxidase inhibitors, mianserin did not increase prolactin response to the 5-hydroxytryptamine (5-HT) precursor tryptophan in nine patients with major depression. Antidepressant drugs apparently produce dissimilar effects on this aspect of brain 5-HT function in depressed patients.